Ley de simplicidad y progresividad tributaria y su impacto en el desarrollo económico de las empresas del sector comercial de Pasaje. - Jiménez Jiménez, Judith Elizabeth (My University, 2021)
In the commercial sector of the city of Pasaje, a multitude of companies are developed in different areas and economic activities; of which one of the main sources of employment, capital flows and exchange of products are commercial companies; They are obliged to pay tributes and taxes; being the most affected by the reforms in tax matters. The problematic situation is the lack of knowledge about the impact on business development of the tax simplicity and progressivity law. The objective of this research work is to analyze the impact of the tax simplification and progressivity law on the economic development of the commercial sector of the Pasaje canton, through descriptive research to propose improvements to current tax policies. A longitudinal descriptive and explanatory methodology is applied to obtain information through an interview, observation and interpret it through comparative analysis and inferential statistics by detailing how the new tax reforms affect commercial companies in the Pasaje canton. In the interviews, the opinions of experts on the subject are expressed, who analyze the impact it will have on the sector. From the economic perspective, production is decreasing, the decrease in sales volume translates into lower income, lower profitability and an increase in unemployment due to the crisis caused by Covid 19; Compared to taxes, as sales revenue, operating costs, market depreciation, and inflation decrease, it also decreases; In general, the law will only hinder local investment and reduce profits by eliminating deductibles and exemptions, creating resistance or other annoyances, such as finding new forms of tax evasion, thinking that they are unnecessary and unhealthy, what the business sector needs is financing , flexibility and vitality to grow and implement improvements in the organization, increase its contribution in the context of socio-economic development.
En el sector comercial de la ciudad de Pasaje, se desarrollan multitud de empresas en distintos ámbitos y actividades económicas; de las cuales una de las principales fuentes de empleo, flujos de capital e intercambio de productos son las empresas comerciales; mismas que están obligadas a pagar tributos e impuestos; siendo las más afectadas por las reformas en materia tributaria. La situación problemática es el desconocimiento sobre el impacto en el desarrollo empresarial de la ley de simplicidad y progresividad tributaria. El objetivo del presente trabajo investigativo es Analizar el impacto de la ley de simplificación y progresividad tributaria en el desarrollo económico del sector comercial del cantón Pasaje. Se aplica una metodología del tipo descriptiva y explicativa, de carácter longitudinal para obtener información a través de una entrevista, observación e interpretarlos mediante análisis comparativos y estadística inferencial al detallar cómo afectan las nuevas reformas tributarias en las empresas comerciales del cantón Pasaje. En las entrevistas se expresa las opiniones de expertos en el tema, quienes analizan el impacto que tendrá en el sector. Desde la perspectiva económica la producción va en decrecimiento, la disminución en volumen de ventas se traduce como menores ingresos, menor rentabilidad e incremento en el desempleo ante la crisis causada por el Covid 19; En comparación con los impuestos, a medida que disminuyen los ingresos por ventas, los costos operativos, la depreciación del mercado y la inflación, también disminuye; en general, la ley solo obstaculizará la inversión local y reducirá las ganancias al eliminar deducibles y exenciones, creando resistencias u otras molestias, como encontrar nuevas formas de evasión fiscal, pensando que son innecesarias y poco saludables, lo que el sector empresarial necesita es financiamiento, flexibilidad y vitalidad para crecer e implementar mejoras en la organización, aumentar su contribución en el contexto del desarrollo socioeconómico.
Keywords: REFORMAS TRIBUTARIAS; OBLIGACIONES TRIBUTARIAS